The Socioeconomic Impact Of Tourism In Chamba District Of Himachal Pradesh - Aman Kumar, Dr. Sunil Kumar (International Journal of Advanced Science and Technology, 2020)
Shimla Nahi basna, Kasauli Nahi basna, Chamba jaroor basna” is one of the famous folklores. From a tourism point of view, Chamba is a preferred tourism destination for people of all age groups due to the vast availability of tourism resources i.e. Museums, temples, mountains, lakes, dams, emporiums, monuments and palaces. In Chamba Pahari, Hindi and Punjabi language are spoken. This beautiful place is more popular amongst domestic tourists because of the historic significance of its temples. People from all over India and World visit the Maa Chamunda Devi Temple to complete their Yatra of Maa Goddess (pilgrimage). Chamba offers the advantage of a one-stop destination from peace lovers to Adventurist. The abundance of tourism products makes it an attractive destination. Chamba is a beautiful village located in Tehog Tehsil of Himachal Pradesh. Chamba district is on the bank of the Ravi River, known for its famous Hindu temples i.e. Shri Chamunda Devi Temple... Chamba was ruled by 67 Kings, before to be merged in the Union of India in April 1948. Chamba is better known for its beautiful artifacts and culture.